Management of the Traditional Knowledge in the Field of the Expressions of Folklore and the Art - Borisova, Vladya (Research Papers, 2005)
The presented article concerns interesting and significant question for the both the theory and the practice as such the field of intellectual property in particular and the economy as whole. This research submits, discusses and suggests a general analysis for so called new objects of intellectual property named traditional knowledge. The major characteristics and specifics of the object have been examined and considered while the accent has been referred to the traditional knowledge in the field of the expressions of folklore and the art.The fundamental framework drawing the contents parameters of the object has been created. The definitions for the different elements of the traditional knowledge, direct or indirect which established them as the object of intellectual property have been given. The collaboration between the traditional knowledge and the cultural heritage of the community has been indicated and proved. The traditional knowledge has been presented as the competitive advantage of the community and as a result of this their economic significance as object of intellectual property has been emphasized.As thus the research embodied the existing and the potential possibilities of the forms and manners for management of the traditional knowledge in the field of the expressions of folklore and the art. There are offered several models of management submitted to the actual economic or society interest. The article suggests specific approach in understanding the phenomenon traditional knowledge and more precise their economic and socio-culture significance.